Policy Implications for Social Development Management in the Context of Digital Transformation in Ho Chi Minh City, Binh Duong, and Tay Ninh Province - Huu Hoang, Nguyen; Van Huan, Tran (VNU Journal of Science: Policy and Management Studies, 2023)
Social development management in the context of digital transformation is a new issue in Vietnam. From a cross-sectional study that includes a survey of 438 civil officials and 450 individuals in Ho Chi Minh City, Binh Duong, and Tay Ninh province, this article analyzes the current state of social development management on six dimensions: Sustainable poverty reduction; health care; education and training; gender equality; social safety, human security and the effectiveness and efficiency of management of the public apparatus in the digital transformation process. The results show that two subject groups gave good and positive evaluation of social development management in these six dimensions. Yet, the two dimensions with the lowest ratings for social development management in the digital age are education and training and health care. The study also recommends that more attention should be given to socially disadvantaged groups to reduce inequality and digital gap in the digital transformation process. Keywords: Digital inequality, policy, digital transformation, social development management, digital gap.